2020
DOI: 10.1002/bse.2626
|View full text |Cite
|
Sign up to set email alerts
|

Shareholders' environmental profile and its impact on firm's environmental proactivity: An institutional approach

Abstract: Theorists and practitioners still argue about different shareholders' environmental preferences. Drawing on various processes of institutional theory such as deinstitutionalization and defensive institutionalism, we test the differences between foreign and national shareholders' influences on firms' environmental proactivity. Specifically, we focus on the country of origin of the dominant shareholders and the environmental culture of the countries of origin of the shareholders. Using unbalanced panel data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 91 publications
0
24
0
1
Order By: Relevance
“…Many internal and external factors also affect CEP. With reference to related studies, this study controls the factors from the following four main aspects (Bueno‐Garcia et al., 2021; Calza et al., 2016; Gonzalezbenito & Gonzalezbenito, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Many internal and external factors also affect CEP. With reference to related studies, this study controls the factors from the following four main aspects (Bueno‐Garcia et al., 2021; Calza et al., 2016; Gonzalezbenito & Gonzalezbenito, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Firm size is the natural logarithm of total assets (García‐Sánchez, Martín‐Moreno, et al, 2021; Ren et al, 2021). ROA is net income divided by total assets (Bueno‐Garcia et al, 2021; Gerged et al, 2021; Ren et al, 2021). Free cash flow is cash flow from operating activities divided by total assets (Kong et al, 2020; Lewandowski, 2017; Trumpp & Guenther, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…(e.g., Bueno-Garcia et al, 2021;Madsen & Ulhøi, 2001). Similarly, studies examining the effect of institutional investors' environmental pressure on CES suggested a positive effect due to firms' dependency on investors.…”
Section: Owner's Powermentioning
confidence: 99%